(untitled) (Physical Education, Health and Social Sciences, 2026)
Multidrug-resistant tuberculosis (MDR-TB) continues to challenge global health due to prolonged, toxic, and poorly effective conventional regimens that fail to achieve sustained therapeutic concentrations at the primary infection site within alveolar macrophages. This review comprehensively examines the formulation, design, and translational potential of nano-liposomal drug delivery systems as a targeted pulmonary platform for MDR-TB therapy. Liposomes, composed of saturated phospholipids and cholesterol, enable simultaneous encapsulation of both hydrophilic and lipophilic anti-TB agents while providing excellent biocompatibility and tunable release kinetics. Optimized particle sizes (100–200 nm) facilitate deep-lung deposition and efficient macrophage phagocytosis, while surface functionalization with mannose or fucose ligands enables active receptor-mediated targeting to CD206 and DC-SIGN receptors overexpressed on infected macrophages. Advanced manufacturing using microfluidics ensures monodisperse, high-encapsulation-efficiency vesicles, and spray-drying with force-control agents produces stable dry-powder inhaler formulations with ideal mass median aerodynamic diameters (1–5 µm). Stimuli-responsive designs incorporating pH-sensitive malachite green or enzyme-cleavable polyphosphate coatings trigger rapid intracellular drug release within the acidic phagolysosome. Clinical evidence from the Phase 3 CONVERT trial of amikacin liposome inhalation suspension (ALIS) demonstrated significantly higher culture conversion rates (29% vs 8.9%) with acceptable safety, while preclinical fucosylated bedaquiline liposomes achieved 6-fold higher lung bioavailability and markedly reduced systemic metabolite exposure. Nano-liposomal systems therefore offer a versatile, macrophage-targeted strategy capable of overcoming intracellular persistence, shortening treatment duration, minimizing toxicity, and combating MDR-TB resistance.